The Knowledge and Attitudes of Families Regarding Elderly Fall Prevention in Pahlawan Binjai Village - Rosmega; Indra Agussamad; Zuraidah Zuraidah; Zulkarnain Batubara (Talenta Publisher, 2020)
Knowledge is the result of know that going after someone makes a sensing of a particular object. While the attitude of the views or feelings that accompanied the tendency to act. If knowledge of a person's behavior, the better it would be even better. However, knowledge is either not accompanied with the attitude that knowledge would be meaningless. This study aims to describe a family of knowledge on the prevention of falls in older adults and family attitudes about the prevention of the incidence of falls in older adults at Kelurahan Pahlawan Binjai. This study was used a descriptive design with a purposive sampling technique involving 71 respondents conducted in April 2012. All respondents answered a questionnaire that was given to the respondents.